Analisa Pemborosan Biaya Pada Proyek Pembangunan PT. Fortindo Mengunakan Metode Rekayasa Nilai (Value Engineering) - Reza Dani Ryanda; Monita Rahayu; Ladika Ladika (Universitas Islam Syekh Yusuf Tangerang, 2023)
The construction of a factory building often requires large costs. This is due to the lack of attention paid to the effectiveness and efficiency of the use of materials, materials and also from the implementation method which is almost the same but in terms of costs it is more economical. The large amount of funding in the construction of factory buildings is an attraction for further analysis with the aim of finding materials and also implementation methods that require more economical costs than before. The purpose of this research is to find savings in construction costs, especially in architectural work by replacing the initial design with a new alternative design. This study uses the Value Engineering method. Based on the results of the analysis, it can be concluded that in architectural work, the largest construction cost lies in wall work, which costs Rp. 1,649,566,000 and floor work which cost Rp. 1,509,219,969. the results of the job function analysis show that the wastage of costs in architectural work lies in wall work and floor work. Where, work items with C/W > 2 include: wall work: C/W = 3.1 and floor work: C/W = 2.15